Analysis of Cognitive Functions in Population Having Major Depressive Disorders - Sharma, Sunidhi; Kacker, Sudhanshu; Saboo, Neha (Journal of College of Medical Sciences-Nepal, 2025)
Background Major Depressive Disorder (MDD) is a complex mental health disorder that has an impact on many facets of cognitive performance. MDD's cognitive symptoms might lead to overall impairments in daily functioning and quality of life. It's vital to remember that the severity and appearance of these cognitive symptoms can differ from person to person. The aim of this study is to assess the cognitive function (attention, learning, memory, decision making and executive functions) in major depressive disorder individuals. Methods The study was conducted in the Department of Physiology, RUHS College of Medical Sciences and associated hospitals on 90 subjects having major depressive disorder of either sex in the age group 20-40 years. Cognitive function parameters (Mini mental status examination, Montreal cognitive protocol A & B, P300 latency, and amplitude) were assessed and data were presented as mean, standard deviation (SD) and correlation coefficient was found using Pearson correlation, and p-value<0.05 considered as statistically significant. Results The mean score of cognitive parameters was increased which was shown as decrease in score of Montreal cognitive assessment (11.22±2.73), mini mental status examination (10.19±1.56). Delay in P300 latency (401.38±11.30) was also seen with increase in Hamilton D (18.33±6.7) score with correlation coefficient r= 0.758. Conclusions A strong positive correlation was observed between the Hamilton Depression (HAM-D) score and cognitive function parameter (P300), indicating that greater severity of depression is associated with a decline in cognitive performance. The relationship between depression and cognitive function is complex and varies among individuals.